2002
DOI: 10.1103/physreva.66.053810
|View full text |Cite
|
Sign up to set email alerts
|

Spatial antibunching of photons with parametric down-conversion

Abstract: The theoretical framework behind a recent experiment by Nogueira et al. [Phys. Rev. Lett. 86, 4009 (2001)] of spatial antibunching in a two-photon state generated by collinear type II parametric down-conversion and a birefringent double-slit is presented. The fourth-order quantum correlation function is evaluated and shown to violate the classical Schwarz-type inequality, ensuring that the field does not have a classical analog. We expect these results to be useful in the rapidly growing fields of quantum ima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…A more comprehensive study of these far field correlations were made by Grayson and Barbosa [10]. Experiments exploring interference at a double slit experiment using twin photons and coincidence counting came in 1994 [13] and 1995 [14] and was further investigated in later work [50,34,19,17,51,52,53,18,54,55]. In this section, we review some of the key experiments exploring aspects of interference of photon pairs using a double slit.…”
Section: Double Slit Experiments With Twin Photonsmentioning
confidence: 99%
See 2 more Smart Citations
“…A more comprehensive study of these far field correlations were made by Grayson and Barbosa [10]. Experiments exploring interference at a double slit experiment using twin photons and coincidence counting came in 1994 [13] and 1995 [14] and was further investigated in later work [50,34,19,17,51,52,53,18,54,55]. In this section, we review some of the key experiments exploring aspects of interference of photon pairs using a double slit.…”
Section: Double Slit Experiments With Twin Photonsmentioning
confidence: 99%
“…The π/2 phase factors are due to the delay introduced by the zero-order quarter-wave plates. The coincidence probability is [18,19] …”
Section: Spatial Antibunchingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that spatial antibunching is a purely quantum property with no classical analog. 30,31 Thus the singlet-beam is inherently nonclassical.…”
Section: Two-photon Singlet Beamsmentioning
confidence: 99%
“…However, because of the antisymmetry of the transverse spatial component, which is provided by the odd pump beam together with the reflection of one photon at the beam splitter, the photons are spatially separated in the y-direction and thus do not occupy the same plane wave mode. Interestingly enough, this characteristic guarantees that the singlet beam exhibits spatial antibunching, a quantum effect with no classical analog [13,14].…”
mentioning
confidence: 99%